Settler States And Customary Law: Indigenous Land Rights in the United States, Canada, Australia and New Zealand - Sanders, Douglas (Journal of Malaysian and Comparative Law, 2019)
Indigenous people exist in all parts of the world. They are population groups which predate the present state formation and the immigration of other peoples.